Determinants of Environmental Performance: The Application of Environmental Management Accounting as a Mediation Variable - Sopia, Iklima Pila; Herianti, Eva; Asmanah, Siti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Conventional management accounting cannot provide information about environmental costs and ignores environmental impact reports. To overcome those weaknesses, Environmental Management Accounting (EMA) can provide data transition from financial accounting, cost accounting, and material flow management to improve material efficiency, reduce environmental impacts and reduce environmental costs. Objective; this study is to examine and evaluate the effect of stakeholder pressure, organizational size, top management commitment, and environmental uncertainty and focus on EMA application as a mediation variable on environmental performance. The sampling method uses Stratified Random Sampling on the one (1) to five (5) star hotels in Bogor City with a total of 52 samples. The data analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) using the Smart PLS application. Research result; the hypothesis testing proves that stakeholder pressure, organizational size, top management commitment, and EMA implementation affect environmental performance. Then the EMA implementation as a mediation variable can influence the relationship between stakeholder pressure, organizational size, and top management commitment to environmental performance. In addition, environmental uncertainty does not affect environmental performance, and the application of EMA cannot mediate the relationship between environmental uncertainty and environmental performance. Limitations; the research carried out during the Covid-19 pandemic resulted in the limited distribution of questionnaires and was sometimes obstructed by the implementation of Large-Scale Social Restrictions (LSSR).